2016
DOI: 10.17221/134/2015-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Callus induction and frond regeneration in Spirodela polyrhiza

Abstract: Wang Y. (2016): Callus induction and frond regeneration in Spirodela polyrhiza. Czech J. Genet. Plant Breed., 52: 114-119.Spirodela polyrhiza belongs to the family Lemnaceae (duckweed), which is a group of small aquatic plants offering an attractive plant expression system for the production of recombinant protein. No frond regeneration protocol has been established in this species yet. An efficient protocol for plant regeneration through organogenesis has been developed in Spirodela polyrhiza for the first ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
0
6
0
8
Order By: Relevance
“…Second, an optimized callus induction protocol can be used. Recently, a study showed that optimizing the callus induction medium can significantly increase the rate of callus induction in S. polyrhiza (Wang, ). Our preliminary results also showed that using the optimized medium reported from Wang () can result in 100% callus induction among all 16 tested S. polyrhiza genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, an optimized callus induction protocol can be used. Recently, a study showed that optimizing the callus induction medium can significantly increase the rate of callus induction in S. polyrhiza (Wang, ). Our preliminary results also showed that using the optimized medium reported from Wang () can result in 100% callus induction among all 16 tested S. polyrhiza genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study showed that optimizing the callus induction medium can significantly increase the rate of callus induction in S. polyrhiza (Wang, ). Our preliminary results also showed that using the optimized medium reported from Wang () can result in 100% callus induction among all 16 tested S. polyrhiza genotypes. It seems plausible that the optimization of the callus induction medium can be used to increase the callus induction efficiency also in other Lemna species.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have implemented callus induction on species within Lemnoideae and have revealed that both the type and concentration of PGRs can significantly enhance the callus induction rate [ 25 , 30 , 31 ]. A crucial role is played by 2,4-D in callus induction in many plant species [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A indução de calos também se mostrou possível a partir da combinação de mais de dois reguladores, como no caso da indução em Spirodela polyrhiza (Wang, 2016). O trabalho, utilizou ANA, TDZ e 2,4 D. Yang et al (2018b) apontaram em seu trabalho que a indução de calos em S. polyrhiza ocorre de maneira mais eficiente quando a concentração de auxina for igual ou superior a de citocinina.…”
Section: Indução De Calosunclassified
“…O primeiro relato de regeneração de folhas de S. polyrhiza foi descrito por Wang (2016) As idades dos calos testados também interferiram nos resultados de eficiência de regeneração. O genótipo L. minor 8627 apresentou regeneração em todas as idades de calos testadas, e maior número de plantas (88%) a partir de calos no início de R2 -com cerca de 120 a 130 dias desde a inoculação, e no fim do subcultivo R2 -com cerca de 140 a 150 dias desde a inoculação.…”
Section: Regeneração De Plantas a Partir De Calosunclassified